Global, regional, and national burdens of ischemic heart disease in the older adults aged 60–89 years: a systematic analysis for the Global Burden of Disease Study 2019 - Zhi, Hao; Yang, Yuedong; Zhao, Juan; Mao, Chenhan; Shen, Jianping; Wang, Xindong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIschemic heart disease (IHD) places a heavy burden on individual and public health. Nevertheless, comprehensive assessments of the burden of IHD in the elderly are absent. It is imperative to update the burden of IHD in older adults and predict the trends.MethodsThe absolute numbers and age-standardized rates (ASRs) of prevalence, mortality, and disability-adjusted life-years (DALYs) for IHD among people aged 60–89 years from 1990 to 2019 were analyzed based on the Global Burden of Disease Study 2019 (GBD 2019). Joinpoint regression analysis was utilized to evaluate the epidemiologic trend of IHD in the elderly from 1990 to 2019. Bayesian age-period-cohort model was used to predict the burden of IHD among the elderly from 2020 to 2034.ResultsAge-standardized prevalence rate (ASPR), age-standardized incidence rate (ASIR), age-standardized DALY rate (ASDR), and age-standardized mortality rate (ASMR) of IHD in older adults have declined slightly over the past 30 years. In 2019, the ASPR, ASIR, ASDR, and ASMR among the elderly with IHD were 14,280.53 (95% UI, 12,301.34–16,610.6), 1,445.21 (1,142–1,793.58), 11,225.74 (10,342.09–11,960.64), and 675.24 (614.21–721.75) per 100,000. The burden of IHD was significantly higher in older men than in women during the study period. In terms of socio-demographic index (SDI), countries and territories with lower SDI bore a more severe burden of IHD. The burden of IHD in the elderly varied considerably across countries. Uzbekistan had the largest increase in rates of prevalence, incidence, DALY, and mortality. The projections show a downward trend in DALY and mortality rates for IHD in older adults from 2020 to 2034, but incidence and prevalence will increase.ConclusionFrom 1990 to 2019, the worldwide burden of IHD among the elderly witnessed a decline. The IHD burden varied significantly across countries and territories. Policymakers should rationalize the allocation of health resources and implement effective prevention and treatment strategies to reduce the burden of IHD among the elderly in economically less developed countries and regions.